Importance of VIIIa Inactivation in a Mathematical Model for the Formation, Growth, and Lysis of Clots. (31st July 2014) - Naidu, P. P.; Anand, M.
Abstract : We perform a sensitivity analysis for a thus far unstudied mathematical model for the formation, growth and lysis of clots in vitro. The sensitivity analysis procedure uses an ensemble standard deviation for species concentrations, and is equivalent to a variance decomposition procedure also available in the literature. Our analysis shows that fibrin production is most sensitive to the rate constant governing activation of prothrombin to thrombin. Further, the time-averaged sum of all species' concentrations is most sensitive to the rate constants governing the inactivation of VIIIa (intrinsic as well as by APC). We therefore conclude that the rate constants for VIIIa inactivation affect the model the greatest: this conclusion must be experimentally verified to determine if such is indeed the case for hemostasis.